2011
DOI: 10.1038/modpathol.2011.51
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, molecular pathology and potential clinical significance of partial chromosome 3 aberrations in uveal melanoma

Abstract: The clinical significance of partial chromosome 3 alteration in uveal melanoma is still not clear. Also, the reported frequencies vary considerably in the published literature from 0 to 48%. The aims of the following study were to identify the frequency, molecular pathology and potential clinical significance of partial chromosome 3 alteration in uveal melanoma. We studied 47 uveal melanomas with an average follow-up of 36 months. Of these, 14 had confirmed metastasis. Allelic imbalance/loss of heterozygosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 24 publications
(44 reference statements)
2
28
1
Order By: Relevance
“…Some of the variability in the results is influenced by differences in methodology for detection and interpretation of changes in parts of chromosome 3 (gains and losses). 49,52 Data from several studies have indicated that partial loss of chromosome may not be as deleterious as total loss of chromosome 3 in influencing the risk of metastasis because tumors with partial chromosome 3 loss behave similar to tumors classified as disomic. 48,49,52 Our study further underscores the need for standardization of techniques, if results from various centers are to be directly compared.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the variability in the results is influenced by differences in methodology for detection and interpretation of changes in parts of chromosome 3 (gains and losses). 49,52 Data from several studies have indicated that partial loss of chromosome may not be as deleterious as total loss of chromosome 3 in influencing the risk of metastasis because tumors with partial chromosome 3 loss behave similar to tumors classified as disomic. 48,49,52 Our study further underscores the need for standardization of techniques, if results from various centers are to be directly compared.…”
Section: Discussionmentioning
confidence: 99%
“…6). Most recent studies consistently show that these tumors, in contrast to those with monosomy 3, are associated with good prognosis 5,6 .…”
mentioning
confidence: 98%
“…In UM there is ample evidence of the association of the primary tumor’s molecular genetics with early development of metastasis, usually within 3 years of diagnosis (Abdel-Rahman et al, 2011; Shields et al, 2011). However, this is the first report linking the molecular genetic alterations of the metastatic lesions with overall tumor progression and patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic studies of the smallest regions of deletion in UM have found multiple regions in chromosome 3 on both the p and q arms; however, these regions don’t generally overlap between different studies(Abdel-Rahman et al, 2011; Hausler et al, 2005; Parrella et al, 2003; Tschentscher et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation